Apomorphine Subcutaneous Infusion is More Efficient Than foslevodopa/foscarbidopa Subcutaneous Infusion in the Treatment of Advanced Parkison´s Disease for the Spanish National Health System - Gonzalez J; Darna J; Mata M (Journal of Public Health International, 2026)
Objectives Motor fluctuations and non-motor disorders not manageable by first-line treatments in advanced Parkinson's disease require continuous dopaminergic stimulation strategies such as subcutaneous infusions of apomorphine (APO) or foslevodopa/foscarbidopa (FLD/FCD). A Budget Impact Analysis (BIA) was performed to estimate the cost difference between both treatments assuming equivalent clinical efficacy and safety. Material and methods The efficacy results of pivotal clinical trials at 12 and 52 weeks of treatment and the safety profile of APO vs FLD/FCD were compared, based on latest scientific publications and other available clinical data. A comparative BIA was performed, based on estimated annual drug treatment costs at Spanish published prices. Results The efficacy of APO (16 h/day) and FLD/FCD (24 h/day) in reduction of OFF hours (2.47 vs 2.75, 12 weeks; 3.66 vs 3.50, 52 weeks; respectively) and increase of ON hours without disabling dyskinesias (2.77 vs 2.72, 12 weeks; 3.31 vs 3.80, 52 weeks; respectively) could be considered clinically equivalent, as well as their safety profiles. However, a significant discrepancy is observed in the costs of the aforementioned alternatives. Considering published prices and the average dose reported in the literature, in Spain the annual cost of APO would be €13,980 compared to €55,198 for FLD/FCD. Consequently, the financial resources required for the treatment of FLD/FCD would enable the treatment of approximately three to four patients with APO. The BIA indicated the potential for annual savings in more than €2,500 million, considering a total target population of over 60,000 patients per year. Finally, an univariant sensitivity analysis was performed, considering a scenario in which the hospital acquisition cost of FLD/FCD decreased between 20%-30% (€44,159- €38,638/year). In this scenario, the total annual savings range between €1,875-€1,532 million per year. Conclusions Overall APO is more efficient than FLD/FCD, as it provides similar clinical efficacy at a lower treatment cost. The selection of an appropriate treatment option is to be determined by clinical criteria and patient characteristics, but cost evaluation should be considered to select the most cost-effective therapeutic option.
Keywords: Parkinson’s disease